A positive perspective of knowledge, attitude, and practices for health-promoting behaviors of adolescents with congenital heart disease. (1st March 2018) - Huang, Hui-Ru; Chen, Chi-Wen; Chen, Chin-Mi; Yang, Hsiao-Ling; Su, Wen-Jen; Wang, Jou-Kou; Tsai, Pei-Kwei
Abstract: Background: Health-promoting behaviors could serve as a major strategy to optimize long-term outcomes for adolescents with congenital heart disease. The associations assessed from a positive perspective of knowledge, attitudes, and practice model would potentially cultivate health-promoting behaviors during adolescence. Aim: The purpose of this study was to examine the relationships between disease knowledge, resilience, family functioning, and health-promoting behaviors in adolescents with congenital heart disease. Methods: A total of 320 adolescents with congenital heart disease who were aged 12–18 years were recruited from pediatric cardiology outpatient departments, and participated in a cross-sectional survey. The participants completed the Leuven Knowledge Questionnaire for Congenital Heart Disease; Haase Adolescent Resilience in Illness Scale; Family Adaptability, Partnership, Growth, Affection, and Resolve; and Adolescent Health Promotion scales. The collected data were analyzed using descriptive statistics and three multiple regression models. Results: Greater knowledge of prevention of complications and higher resilience had a more powerful effect in enhancing health-promoting behaviors. Having symptoms and moderate or severe family dysfunction were significantly more negatively predictive of health-promoting behaviors than not having symptoms and positive family function. The third model explained 40% of the variance in engaging in health-promoting behaviors among adolescents with congenital heart disease. Conclusion: The findings of this study provide new insights into the role of disease knowledge, resilience, and family functioning in the health-promoting behavior of adolescents with congenital heart disease. Continued efforts are required to plan family care programs that promote the acquisition of sufficient disease knowledge and the development of resilience for adolescents with congenital heart disease.